Fas (CD95) expression in myeloid cells promotes obesity‐induced muscle insulin resistance. Issue 1 (6th November 2013) - Wueest, Stephan; Mueller, Rouven; Blüher, Matthias; Item, Flurin; Chin, Annie S H; Wiedemann, Michael S F; Takizawa, Hitoshi; Kovtonyuk, Larisa; Chervonsky, Alexander V; Schoenle, Eugen J; Manz, Markus G; Konrad, Daniel
Abstract Low‐grade inflammation in adipose tissue and liver has been implicated in obesity‐associated insulin resistance and type 2 diabetes. Yet, the contribution of inflammatory cells to the pathogenesis of skeletal muscle insulin resistance remains elusive. In a large cohort of obese human individuals, blood monocyte Fas (CD95) expression correlated with systemic and skeletal muscle insulin resistance. To test a causal role for myeloid cell Fas expression in the development of skeletal muscle insulin resistance, we generated myeloid/haematopoietic cell‐specific Fas‐depleted mice. Myeloid/haematopoietic Fas deficiency prevented the development of glucose intolerance in high fat‐fed mice, in ob/ob mice, and in mice acutely challenged by LPS. In vivo, ex vivo and in vitro studies demonstrated preservation of muscle insulin responsiveness with no effect on adipose tissue or liver. Studies using neutralizing antibodies demonstrated a role for TNFα as mediator between myeloid Fas and skeletal muscle insulin resistance, supported by significant correlations between monocyte Fas expression and circulating TNFα in humans. In conclusion, our results demonstrate an unanticipated crosstalk between myeloid cells and skeletal muscle in the development of obesity‐associated insulin resistance.